Effectiveness of Afrocentric Counselling-Based Interventions on Eco-Consciousness and Life Skills Development among In-School Adolescents in South West Nigeria - ADESEHINWA, Olayinka A.; OKEOWO, Adegoke O.; OLAWALE, Sunday G.; OLAWOYIN, Alimat A. (Ilorin Journal of Education, 2025)
This study investigated the effectiveness of three Afrocentric counselling-based interventions—Eco-Oriented Counselling (EOC), Cognitive-Behavioural Eco-Counselling (CBEC), and Indigenous Life Skills and Eco-Counselling (ILSEC)—on eco-consciousness and life skills development among in-school adolescents in Nigeria, using a 3 × 3 × 3 factorial experimental design. A total of 192 participants were randomly assigned to control and intervention groups. Pre-test and post-test assessments were conducted using validated scales. Results from paired-samples and independent-samples t-tests revealed significant improvement in both experimental and control groups; however, the experimental group demonstrated a significantly greater mean change (M = +27.84, t = 11.65, p < .05) compared to the control group (M = +9.91, t = 3.62, p < .05), supporting the first hypothesis. A one-way ANOVA revealed significant differences in post-test scores among the three intervention groups, F(2, 169) = 40.26, p < .001, η² = .323. Tukey HSD post hoc analysis revealed that EOC was the most effective, followed by CBEC, with ILSEC being the least effective. These findings confirm that Afrocentric interventions, particularly EOC, significantly enhance eco-consciousness and life skills. The study highlights the importance of culturally grounded, contextually relevant counseling approaches in fostering adolescent development in African settings.